Back Cover: Plasma Process. Polym. 8∕2014. Issue 8 (August 2014) - Burmaka, Gennady; Denysenko, Igor B.; Ostrikov, Kostya (Ken); Levchenko, Igor; Azarenkov, Nikolay A.
<x xml:space="preserve">Abstract</x> Back Cover: The growth mechanism was clarified and differences between the plasma‐ and neutral gas‐grown carbon nanotubes were explained by using an enhanced large‐scale model and numerical simulation technique. The nanotubes synthesized by plasma process can be longer than those synthesized by neutral gas technique. The low‐temperature growth of the nanotube array is also possible when the hydrocarbon ion flux to the nanotubes dominates over fluxes of other species. Further details can be found in the article Gennady Burmaka et al. on page 798. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>